Capturing the magic of carbon dioxide: Engaging hands-on demonstrations to explain geological storage. Issue 2 (1st October 2019) - Feitz, Andrew; Hovorka, Susan; Lehane, Kate
Global implementation of geological storage of carbon dioxide (CO2) is one of the proposed methods to help reduce greenhouse gas emissions and avoid the worst effects of future climate change. However, conveying the benefits of carbon capture and storage (CCS) technology is a real challenge. In this article we explore the use of theatrical demonstrations that allow the public to interact with and control the behaviour of CO2 to reduce barriers to the technology. Engaging hands-on demonstrations offer the opportunity to 'explain the magic' and reinforce key concepts for the safe and effective storage of greenhouse gases.